2010
DOI: 10.1149/1.3247345
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of MOCVD ZnO TFTs on Glass Substrates with Nitrogen-Rich Silicon Nitride Gate Dielectric

Abstract: Thin-film transistors ͑TFTs͒ on glass substrates were fabricated using ZnO, grown by a metallorganic chemical vapor deposition ͑MOCVD͒ technique, with N-and Si-rich silicon nitrides as gate dielectrics. This is a report on MOCVD-grown ZnO TFTs that use silicon nitride as gate dielectrics. The ZnO TFTs using N-rich silicon nitride exhibited a field-effect mobility of 6.5 cm 2 /V s, a subthreshold slope of 0.8 V/decade, an on/off current ratio of 10 8 , and a threshold voltage of 2.05 V. The performance of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Polycrystalline ZnO-based semiconductor thin films have higher carrier mobility, greater chemical stability, and lower photosensitivity levels than conventional hydrogenated amorphous silicon (a-Si:H) thin films. Therefore, they can replace a-Si:H thin films as the active channel layers in TFTs to improve electrical performance [6][7][8][9][10]. Recently, it has also been demonstrated that they can be used in transparent memory [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Polycrystalline ZnO-based semiconductor thin films have higher carrier mobility, greater chemical stability, and lower photosensitivity levels than conventional hydrogenated amorphous silicon (a-Si:H) thin films. Therefore, they can replace a-Si:H thin films as the active channel layers in TFTs to improve electrical performance [6][7][8][9][10]. Recently, it has also been demonstrated that they can be used in transparent memory [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted considerable attentions as channel layers for metal-insulator-semiconductor field effect transistors (MISFETs). [7][8][9][10][11][12][13][14] Recently, high-quality single crystalline ZnO wafers grown by a hydrothermal method have been commercially available, 15 which enables us to fabricate ZnO-based MISFETs with excellent electrical properties.…”
mentioning
confidence: 99%
“…21,22 This explanation is consistent with our previously published result that the grain size of ZnO films grown on the Si-rich Si 3 N 4 layer is smaller than that of the films grown on the N-rich Si 3 N 4 layer. 8 This is due to the fact that Si-rich Si 3 N 4 films have higher density of Si dangling bonds in comparison with N-rich Si 3 N 4 films. 19,23 Characteristics of ZnO TFTs with SiO 2 /Si 3 N 4 bilayer gate dielectric.- Figure 3a shows the output characteristics ͑drain current ͑I D ͒ versus drain-source voltage ͑V DS ͒͒ of ZnO TFTs using the SiO 2 /Si 3 N 4 bilayer gate dielectric for a gate-source voltage ͑V GS ͒ ranging from 15 to 0 V in steps of −5 V. These devices exhibit clear pinch-off and saturation behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the increasing interest in the ZnO TFTs, various techniques, including molecular beam epitaxy, 1 sputtering, 2,3 pulsed laser deposition, 4 atomic layer deposition, 5 and metallorganic chemical vapor deposition [6][7][8] ͑MOCVD͒, are under investigation to realize ZnO channel layer of the TFTs. Among them, MOCVD has certain advantages, such as good reproducibility, capability of uniformly fabricating thin films of high quality, and the possibility of scaling up the process to commercial base production.…”
mentioning
confidence: 99%
See 1 more Smart Citation